2017
DOI: 10.1007/s40858-017-0147-3
|View full text |Cite
|
Sign up to set email alerts
|

Deoxynivalenol resistance as a component of FHB resistance

Abstract: Fusarium head blight (FHB) is one of the most devastating diseases of wheat (Triticum aestivum), barley (Hordeum vulgare) and other small grain cereals grown in warm and humid regions worldwide. In addition to yield loss, the disease compromises the quality of infected grain as a result of contamination with a range of Fusarium mycotoxins that are harmful to human and animal health. Deoxynivalenol (DON) is the most prevalent trichothecene mycotoxin found in Fusarium-infected grains. DON acts as a virulence fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 74 publications
(87 reference statements)
0
63
0
Order By: Relevance
“…Because the flowering patterns between genotypes were similar in the years analyzed, these differences in mycotoxin contamination could be a result of differences in FHB resistance (polygenic resistance). 34 In 2014, we expected a higher mycotoxin contamination compared to 2015 and 2016, related to the major values of incidence/FHB index observed in the field. In 2014, we observed a slight predominance of F. graminearum respect to F. poae; therefore, we expected to find a major proportion of DON and its acetylated derivatives compared to NIV.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Because the flowering patterns between genotypes were similar in the years analyzed, these differences in mycotoxin contamination could be a result of differences in FHB resistance (polygenic resistance). 34 In 2014, we expected a higher mycotoxin contamination compared to 2015 and 2016, related to the major values of incidence/FHB index observed in the field. In 2014, we observed a slight predominance of F. graminearum respect to F. poae; therefore, we expected to find a major proportion of DON and its acetylated derivatives compared to NIV.…”
Section: Discussionmentioning
confidence: 80%
“…), showing different extents of mycotoxin contamination in each genotype. Because the flowering patterns between genotypes were similar in the years analyzed, these differences in mycotoxin contamination could be a result of differences in FHB resistance (polygenic resistance) …”
Section: Discussionmentioning
confidence: 99%
“…DON resistance is a component of FHB resistance (Gunupuru et al, 2017). We hypothesized that like TaFROG, TaNACL-D1 might enhance both FHB and DON resistance .…”
Section: Tanacl-d1 Enhances Fhb Resistancementioning
confidence: 99%
“…Several studies have associated the ability to conjugate DON into DON‐3‐ O ‐glucose (D3G) with partial resistance towards FHB (for a review, see Gunupuru et al ., ). In particular, Lemmens et al .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have associated the ability to conjugate DON into DON-3-O-glucose (D3G) with partial resistance towards FHB (for a review, see Gunupuru et al, 2017). In particular, Lemmens et al (2005) showed that the presence of the Fhb1 locus was correlated with increased metabolizing of DON into D3G.…”
Section: Introductionmentioning
confidence: 99%